Studi Efektivitas Penambahan Cangkang Kemiri dan Superlasticizer pada Sifat Mekanik Beton - Dahlan, Ayi; Yogaswara, Dendi; Febrijanto, Rudy (Jurnal Konstruksi, 2023)
Candlenut shells are hard and light, so there is potential to obtain a lighter weight concrete structure but of greater quality by partially replacing it or adding coarse aggregate with candlenut shells. In this research, candlenut shells were used as a substitute for coarse aggregate in the concrete mixture. The aim of this research is to determine the mechanical properties (compressive strength, split tensile strength and deflection strength) of concrete with the addition of candlenut shells and superplasticizer. The method used in this research is a quantitative method. The amount of candlenut shell material used is a substitution for the volume of coarse aggregate of 15%, 30% and 45%. There were two types of samples made in this research, including cylindrical samples with a diameter of 15 cm, height 30 cm, and blocks with dimensions of 10 cm x 15 cm x 60 cm. These samples were made for testing the compressive strength of concrete, splitting tensile strength of concrete and deflection strength of concrete. Concrete with the substitute material for candlenut shells is expected to achieve the planned compressive strength target of 20 MPa. Based on the test results for compressive strength, split tensile strength and concrete deflection strength, the average value for each variation was obtained. Mixture 1 (0%) has an average compressive strength value of 25.68 MPa, an average split tensile strength of 2.11 MPa, deflection strength of 2.85 MPa. Mixture 2 (15%) has a compressive strength of 20.28 MPa, split tensile strength of 1.55 MPa, deflection strength of 1.49 MPa. Mixture 3 (30%) has a compressive strength value of 16.64 MPa, split tensile strength 1.41 MPa, deflection strength 1.24 MPa and for Mixture 4 (45%) the compressive strength value is 12.96 MPa, split tensile strength 1.25 MPa, deflection strength 1.00 MPa.